The Observation of Arabic Language Differentiation in the 2013 Curriculum and the "Merdeka" Curriculum - Rara Nur'aini; Mohamad Zaka Al Farisi (Abjadia, 2023)
Indonesian education is in a transition and adaptation period from the K-13 (Kurikulum 2013/2013 Curriculum) to the KM (Kurikulum Merdeka/"Merdeka" Curriculum). So research that compares the two curricula needs to be done to understand the transition of K-13 to KM, especially in Arabic subjects. This research was descriptive-comparative-evaluative research with a content analysis design. Data collection instruments were document studies and semi-structured interviews to explore teacher perceptions regarding those two curricula. In the KM goal component, language skills are expanded into six language elements, listening (istimā'), speaking (kalām), reading-viewing (qirā'ah), and writing-presenting (kitābah). The language skills for viewing and presenting did not exist previously in the K-13. The material components in both curricula still have the same scope. K-13 uses a scientific approach in the strategy component, while KM uses a differentiated learning approach according to student achievement. Then the learning strategies in K-13 are arranged in RPP (Rencana Pelaksanaan Pembelajaran/Learning Implementation Plan), while those for KM are in teaching modules (modul ajar). Then, in the evaluation component, the KKM (Kriteria Ketuntasan Minimal/Minimum Completeness Criteria) changes to the KKTP (Kriteria Ketercapaian Tujuan Pembelajaran/Learning Objectives Achievement Criteria). The information obtained from the interviews shows that the teacher has recently been given freedom in teaching, they experience confusion and are not yet ready. Teachers already understand KM theory but have not been able to implement it ideally. This lack of implementation is due to the influence of the unavailability of Arabic language textbooks based on KM, the unavailability of report cards with an assessment format based on KM, and teachers under the Kemenag (Kementerian Agama/Ministry of Religion) have been unable to take part in the program of guru penggerak (mover teachers) education program.